2018
DOI: 10.1590/1516-4446-2017-2409
|View full text |Cite
|
Sign up to set email alerts
|

Active Brazilian crack cocaine users: nutritional, anthropometric, and drug use profiles

Abstract: This is a pioneering study that examines the nutritional status of crack users. Our results showed that most crack users present normal anthropometric findings and the prevalence of underweight is low. However, blood analysis showed changes and a specific type of malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Low caloric intake, together with abnormal metabolic and gastrointestinal functions, can lead to malnutrition among cocaine users [118]. For example, Escobar et al [119] found that hemoglobin and hematocrit levels in cocaine users were below normal, indicating protein-energy malnutrition and anemia. As the authors pointed out, anemia in this population might be associated with a diet poor in micronutrients (e.g., iron), inadequate protein consumption, and clinical issues such as decreased intrinsic factor secretion, intestinal perforations, and bacterial or infectious diseases.…”
Section: Cocaine and Nutritionmentioning
confidence: 99%
“…Low caloric intake, together with abnormal metabolic and gastrointestinal functions, can lead to malnutrition among cocaine users [118]. For example, Escobar et al [119] found that hemoglobin and hematocrit levels in cocaine users were below normal, indicating protein-energy malnutrition and anemia. As the authors pointed out, anemia in this population might be associated with a diet poor in micronutrients (e.g., iron), inadequate protein consumption, and clinical issues such as decreased intrinsic factor secretion, intestinal perforations, and bacterial or infectious diseases.…”
Section: Cocaine and Nutritionmentioning
confidence: 99%
“…When cocaine is smoked, BE production rates are decreased and higher amounts of anhydroecgonine methyl ester are formed leading to the formation of anhydroecgonine by enzymatic cleavage and spontaneous chemical hydrolysis [21]. The co-consumption of cocaine and alcohol, a known depressant, is one of the most common association among drug users [22]. Since they affect the central nervous system differently, leading the user to feel sober, the risk of overdose is greater than taking the substances separately [23].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were replicated in a study that examined effects of intra-nasally snorted and intravenous cocaine administration [53]. Contrary findings were seen in a study that examined the nutritional status of crack cocaine users in Brazil [54]. The study found that the haematocrit level was less than normal in 36.4% of the sample and haemoglobin was less than normal in 32.4%.…”
Section: Cannabismentioning
confidence: 84%